RESPON BIBIT TANAMAN LADA TERHADAP APLIKASI MIKORIZA INDIGENOUS GULMA - Hasid, Rachmawati; Halim, Halim (Jurnal Agroteknos, 2011)
The research on the response of pepper seedlings to the application of mycorrhiza indigenous of weed has been carried out at Sindang Kasih village of Konawe Selatan district on May until September 2008. The aim of this research was to study response of pepper seedlings to the application of mycorrhiza indigenous of weed. The research used randomized complete design with six treatments and three replications. The treatments were control (M0), 10 grams mycorrhiza indigenous of weed/polybag (M1), 15 grams mycorrhiza indigenous of weed/polybag (M2), 20 grams mycorrhiza indigenous of weed/polybag (M3), 25 grams mycorrhiza indigenous of weed/polybag (M4), 30 grams mycorrhiza indigenous of weed/polybag (M5). The parameters were number of leaves, percentage of infection of mycorrhiza to pepper root and relative field mycorrhiza dependency of pepper. The research showed that the highest number of pepper leaves at the end research was M1 with 12.65 leaves, percentage of infection of mycorrhiza to pepper root was M4 with 96.67 % and the lowest relative field mycorrhiza dependency was M2 with 19.74 %. Key words: mycorrhiza indigenous, weed, pepper, relative field myccorhiza dependency